Plan de comunicación para la unidad de prácticas y vinculación con la sociedad de la carrera comunicación social de la Universidad Politécnica Salesiana sede Quito - Egas Armas, Mishell Fernanda (2015)
The "Communication Plan" issued by the unit practices for entailment with society and is part of the race Communication at the Salesian University Quito headquarters ", aims to create a communication plan that provides updated information about processes and mechanisms that have been taking for the past two years in relation to pre-professionals of the students¨. This research is conducted with the description of concepts and categories of communication and relationship with society from a new perspective of organizational management with the input from various authors and institutional historical knowledge of the Salesian Polytechnic University in the School of Social Communication. The coordination and liaison of the Pre-professional Practices with the Society is an important part of this study. This part of the study becomes an antecedent to make a diagnosis that assesses the current situation and identify areas for improvement through a proposed plan of communication with internal and external actions. The final contribution of this research proposes a communication plan, seeking an articulation inside of the university, in the relations of the teachers with students that strengthen the management doned by the Department of Social Communication of Practices based in the city of Quito, because that coordination is reflected at academic and professional level of the students and teachers form the University.